Multiple genomic features filtration to improve protein-protein interactions prediction - Rosfuzah Roslan, 1984-; Muhamad Razib Othman; Fakulti Sains Komputer dan Sistem Maklumat (2010)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2010